2021
DOI: 10.1186/s13287-020-02094-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D cell culture on bone regeneration potential of mesenchymal stromal cells

Abstract: As populations age across the world, osteoporosis and osteoporosis-related fractures are becoming the most prevalent degenerative bone diseases. More than 75 million patients suffer from osteoporosis in the USA, the EU and Japan. Furthermore, it is anticipated that the number of patients affected by osteoporosis will increase by a third by 2050. Although conventional therapies including bisphosphonates, calcitonin and oestrogen-like drugs can be used to treat degenerative diseases of the bone, they are often a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 133 publications
(153 reference statements)
1
32
0
Order By: Relevance
“…This latter observation may be due to the effect of time reducing Ca 2+ dynamics in untreated ASCs, but not in ASCs undergoing osteogenic differentiation. This is interesting because the manipulation of Ca 2+ signalling has been proposed as a pivotal mechanism for the induction of osteogenic differentiation [20,34,35], leading to the development of electrical stimulation-based systems to promote osteogenic differentiation, as a possible tool for bone regeneration [26,27]. As we have shown that spontaneous Ca 2+ oscillations in untreated ASCs are reduced over time, it is plausible to speculate that external stimuli promoting sustained Ca 2+ oscillations may be responsible for osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This latter observation may be due to the effect of time reducing Ca 2+ dynamics in untreated ASCs, but not in ASCs undergoing osteogenic differentiation. This is interesting because the manipulation of Ca 2+ signalling has been proposed as a pivotal mechanism for the induction of osteogenic differentiation [20,34,35], leading to the development of electrical stimulation-based systems to promote osteogenic differentiation, as a possible tool for bone regeneration [26,27]. As we have shown that spontaneous Ca 2+ oscillations in untreated ASCs are reduced over time, it is plausible to speculate that external stimuli promoting sustained Ca 2+ oscillations may be responsible for osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 85%
“…After 72 h, standard medium was replaced by StemPro ® adipocyte differentiation basal medium supplemented with StemPro ® adipogenesis supplement (Life Technologies, Thermo Fisher Scientific). After 21 days, differentiation was assessed by Oil RedO staining as described earlier [27].…”
Section: Adipogenic Differentiationmentioning
confidence: 99%
“…They are also known as early markers of osteoblast differentiation [ 10 ]. IBPS is known to be expressed in bone, dentin, cementum and calcified cartilage [ 28 , 40 ]. Therefore, we selected those five genes to evaluate osteogenic differentiation by measuring the gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…On this regard, Yang and colleagues developed a 3D culture system in which osteoblasts collected from the long bone of mouse model of Apert syndrome were homogeneously encapsulated in a poly(ethylene glycol)-diacrylate (PEGDA) 3D hydrogel [194]. Various works in literature demonstrated the importance of physical three-dimensionality of the matrix in regulating osteoblast behaviour, including cell osteogenesis and bone matrix formation (see [195] for an up-to-date review). Indeed, the Authors demonstrated that the expression of collagen type-I and -II and osteocalcin was higher, whereas the levels of matrix metalloproteases and the BMP inhibitor Noggin were lower in mutated osteoblasts encapsulated in 3D scaffolds compared with control cells [194].…”
Section: Cell-based Disease Modelling: From 2d To 3d Culture Systemsmentioning
confidence: 99%